THE MODERATING EFFECT OF SALES VOLATILITY IN THE COMPANIES LIST OF SHARIAH SECURITIES DURING THE ERA PANDEMIC - Mursid, Mansur Chadi; Aisah, Nur; Tamamudin, Tamamudin (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
The volatility of sales and cash flow companies during Covid 19 in the world are unstable. This study aims to analyze the moderating effect of sales volatility in the relationship between debt level, company size, and cash flow volatility on profit persistence. We used the interaction method to analyze the companies’ list of sharia securities reports from 2018 to 2022. The results show that debt level positively affects profit persistence. Company size does not effect to profit persistence. Cash flow volatility does not effect to profit persistence. Sales volatility negatively moderates the relationship between debt level and profit persistence. This was interesting to discuss because of the pandemic.